Governing AI for Humanity - United Nations (United Nations, 2024)
The multi-stakeholder High-level Advisory Body on Artificial Intelligence, initially proposed in 2020 as part of the United Nations Secretary-General’s Roadmap for Digital Cooperation (A/74/821), was formed in October 2023 to undertake analysis and advance recommendations for the international governance of artificial intelligence. Artificial intelligence (AI) is transforming our world. This suite of technologies offers tremendous potential for good, from opening new areas of scientific inquiry and optimizing energy grids, to improving public health and agriculture and promoting broader progress on the Sustainable Development Goals (SDGs). Left ungoverned, however, AI’s opportunities may not manifest or be distributed equitably. Widening digital divides could limit the benefits of AI to a handful of States, companies and individuals. Missed uses – failing to take advantage of and share AI-related benefits because of lack of trust or missing enablers such as capacity gaps and ineffective governance – could limit the opportunity envelope. Accountability requires implementation so that commitments to global AI governance translate to tangible outcomes in practice, including on capacity development and support to small and medium enterprises, so that opportunities are shared. Much of this will take place at the national and regional levels, but more is also needed globally to address risks and harness benefits.